The Wolf (Canis lupus) in Greenland: A Historical Review and Present Status - Dawes, Peter R.; Elander, Magnus; Ericson, Mats (ARCTIC, 1986)
In the past few decades, little information on the wolf (Canis lupus) in Greenland has been published. The decline of the species and its extirpation in the late 1930s from East Greenland is well documented. Since then, there has been a tendency for wolves sighted in the North and East Greenland National Park to be classified as temporary visitors wandering afar from adjacent Canada, with no prospect of survival in Greenland for anything but a short period. In view of the virtual absence of human population in this vast region, that assumption may not be accurate. There is now abundant evidence to indicate that a renewed immigration and dispersal of wolves has been taking place during the last years, with a migration route from Ellesmere Island eastward across North Greenland into Peary Land, and then southward into the fjord region of central East Greenland. The wolf is reoccupying its former range and by the winter of 1983 wolves had reached the Scoresby Sund region - the species' southernmost territory of the 1930s. Examination of the published records and all available unpublished data provides a historical picture of the status of the wolf in Greenland, from which some conclusions can be made regarding populations, pack size, migration routes, feeding habits and travelling distances.Key words: wolf, Canis lupus, Greenland, history, distribution, migration, re-establishment, High Arctic Mots clés: loup, Canis lupus, Groenland, histoire, distribution, migration, ré-établissement, nord de l'Arctique